EVALUATION OF SAP IMPLEMENTATION ACCEPTANCE WITH THEORY OF PLANNED BEHAVIOR AT PT KERETA API INDONESIA (PERSERO) - Audhini Salsabilla Syauqie; Warih Puspitasari; Lutfia Septiningrum (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2023)
PT Kereta Api Indonesia (Persero) is a State-Owned Enterprise (BUMN) that has the leading business process to provide, manage, and regulate rail services in Indonesia. SAP is one software that can support the company's business processes. SAP implementation has been carried out since 2012 until now. In implementing a system, success or failure can be assessed on non-technical aspects; namely, the user can accept and operate SAP properly. Thus, this study will analyze the success of SAP implementation, namely how, the attitude of users in accepting the use of SAP at PT Kereta Api Indonesia (Persero) using the theory of planned behavior models. The variables in this study are attitudes, perceived behavioral control, behavioral intentions, subjective norms, and behavior. In this study, behavioral intention and behavior explain how individuals operate SAP. Meanwhile, attitudes, subjective norms, and perceived behavioral control affect the individual's intention to operate SAP, and behavior is influenced by behavioral intentions. Data collection was carried out by distributing questionnaires to a number of respondents, as many as 20 SAP users at PT Kereta Api Indonesia (Persero). Data processing uses smartPLS 3.3.9 with a partial least square (PLS) approach. Hypothesis testing was carried out with a significance level of 0.05, and the results obtained were that attitude (attitude) had a positive and significant effect on behavioral intentions (intentions), behavioral intentions had a positive and significant influence on behavior, subjective norms, and behavioral control had a negative effect on behavioral intentions in using SAP.